Can Non-Urological Doctors Play a Role in Early Prostate Cancer Detection? - Yazici, Cenk Murat; Dogan, Cagri (Urology Journal, 2014)
Abstract Purpose: To evaluate the awareness of non-urological doctors for their role in evaluating prostate cancer (Pca) in scientific manner which may be a possible probability for late diagnosis of Pca. Materials and Methods: A total of 936 non-urological specialists working in 1 university and 4 education and research hospital who were able to evaluate male patients over 50 years of age were included to the survey. A face to face questionnaire had been administered to all participants. Results: A total of 92 (9.8%) participants were evaluating prostate-specific antigen (PSA) level to all their elderly male patients while 404 (43.2%) participants had never made this evaluation. Among the participants who were evaluating PSA, none was performing an informed decision making consult and even they did not have any idea about the meaning of this strategy. About the criteria for urological consultation, 56 (6%) reported that they consult all their elderly male patients, whereas 880 (94%) answered that they perform consultation if their patients has sought help for any urological symptom. Conclusion: Urologists must remind the non-urological specialists that their approaches to Pca evaluation may change mortality rates of this disease and give them proper information about the scientific evaluation of Pca. This may help us to decrease the mortality rates of Pca.